GOOD ELECTORAL GOVERNANCE AND INTEGRITY: ANALYZING THE 2024 LEGISLATIVE VOTE RECAPITULATION PROCESS IN WEST JAVA, INDONESIA - Ratna Istianah; Armin Arsyad; Gustiana Kambo (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The legitimacy of electoral governance strongly depends on the integrity of the vote recapitulation process. This study examines the challenges and dynamics of electoral integrity during the 2024 legislative vote recapitulation process in West Java, Indonesia. Utilizing data from the official evaluation report of the West Java Provincial Election Commission (KPU), the research identifies several institutional, procedural, and technological vulnerabilities that affected the integrity of the recapitulation process. Key issues included technical failures in the Sirekap system, inconsistent data verification, weak inter-institutional coordination, and human resource limitations across election management bodies. Moreover, disputes over vote count results were submitted to the Constitutional Court, indicating areas where procedural integrity was questioned. These findings highlight the need for comprehensive reforms in electoral management bodies, professional capacity development, stronger legal safeguards, and inclusive oversight mechanisms to ensure electoral integrity in Indonesia's evolving democratic landscape.